Isotope Ratios and Chemical Analysis of the 1957 Brazilian Ubatuba Fragment - Powell, Robert M; Swords, Michael; Rodeghier, Mark; Budinger, Phyllis (Journal of Scientific Exploration, 2022)
A sample from the Ubatuba fragment collected in Brazil in 1957 was tested with the intent of examining the isotope ratios of its primary element, magnesium, and the trace elements strontium, barium, copper, and zinc. As background, the history of chemical testing of the Ubatuba fragments during the 1960s-1980s at multiple labs with varying capabilities is reviewed and then the remainder of the paper examines recent tests completed in 2017 and 2018 that for the first time used HR-ICPMS techniques to look at the isotopic ratios of the minor constituents as well as the primary magnesium makeup of the sample. The magnesium isotope ratios were found to fall within terrestrial limits while the results on the isotope ratios of the trace elements was inconclusive. Recommendations are made for improving the process of examining the trace elements. Keywords: Ubatuba, isotope, magnesium, HR-ICPMS, UFO